Professional English in Use Medicine - Glendinning E. H. Eric (Cambridge)
Professional English in Use Medicine contains 60 units covering a wide variety of medical vocabulary. Topics include diseases and symptoms, investigations, treatment, examining and prevention. The book also introduces general medical vocabulary related to parts and functions of the body, medical and para-medical personnel, education and training, research, and presentations. Primarily designed as a self-study reference and practice book, it can also be used for classroom work and one-to-one lessons. Professional English in Use Medicine has been carefully researched using the Institute for Applied Language Studies medical corpus, as well as authentic texts, documents and cases. Professional English in Use Medicine is a must for teachers of medical English and for medical practitioners who need to use English at work, either in their own country or abroad.